The Effectiveness of Local Government Spending on Poverty Rate Reduction in Central Java, Indonesia - Suprih Handayani; Suharno Suharno; Lilis Siti Badriah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
During the 2017-2019 period, Central Java performed well in poverty alleviation. It turns out that the reduction of poverty in Central Java has a major contribution in reducing the poverty rate nationally, Indonesia. This poverty reduction could occur due to an increase in the regional aggregate government expenditure budget in Central Java. This study aimed to determine the effect of regional spending by function on poverty levels in districts/cities in Central Java using panel data regression. The model chosen is the Fixed Effect Model with the SUR approach. The results show that regional spending on health, education, and social protection negatively affects poverty levels. On the other hand, spending in the economic sector has a significant but positive impact on the poverty level. Meanwhile, spending on infrastructure does not show a significant effect on reducing poverty in Central Java. The government needs to maintain financial management in the health, education, and social assistance functions, as well as carry out further studies related to budget allocations in the economic and infrastructure sectors.Keywords: poverty, poverty reduction, government spending, fixed effect model